2011
DOI: 10.1002/j.1551-8833.2011.tb11474.x
|View full text |Cite
|
Sign up to set email alerts
|

Perchlorate, bromate, and chlorate in hypochlorite solutions: Guidelines for utilities

Abstract: Hypochlorite solutions contain oxyhalide species such as perchlorate, chlorate, and bromate that form during and after manufacture. Such oxyhalide species have the potential to contaminate finished drinking water if adequate control measures are not taken to minimize their formation during manufacture, shipment, and storage of hypochlorite solutions. This article describes the rate of formation of perchlorate in hypochlorite solutions and discusses the chemistry behind a series of control strategies that utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 19 publications
(24 reference statements)
5
41
0
3
Order By: Relevance
“…In 2005, the Massachusetts Department of Environmental Protection (MDEP) reported significant levels of perchlorate in commercial solutions of sodium hypochlorite used for water disinfection (levels ranging from 260 to 6 750 μg/L were measured, with concentrations of perchlorate increasing with time of product storage) (MDEP, 2005). Stanford et al (2011) confirmed these findings and estimated that the formation of perchlorate is reduced by a factor of 7 or a factor of 36, when a 2 M solution of hypochlorite is diluted to 1 or 0.5 M, respectively. Further studies were performed to confirm these results.…”
Section: Sources Of Food Contaminationsupporting
confidence: 55%
See 1 more Smart Citation
“…In 2005, the Massachusetts Department of Environmental Protection (MDEP) reported significant levels of perchlorate in commercial solutions of sodium hypochlorite used for water disinfection (levels ranging from 260 to 6 750 μg/L were measured, with concentrations of perchlorate increasing with time of product storage) (MDEP, 2005). Stanford et al (2011) confirmed these findings and estimated that the formation of perchlorate is reduced by a factor of 7 or a factor of 36, when a 2 M solution of hypochlorite is diluted to 1 or 0.5 M, respectively. Further studies were performed to confirm these results.…”
Section: Sources Of Food Contaminationsupporting
confidence: 55%
“…MDEP concluded that these levels could result in a concentration of 0.2-0.4 g/L in drinking water. In addition, Stanford et al (2011) noted an increased decomposition of hypochlorite to perchlorate at temperatures > 15 °C and a pH < 11. Greiner et al (2008) analysed chemicals used for water disinfection collected from 102 different manufacturing locations.…”
Section: Sources Of Food Contaminationmentioning
confidence: 98%
“…We compared these results with those of tap water from different regions of Italy and we found that in all cases values of these latter were higher than those of bottled water (roughly one order magnitude) probably because of different conditions of the water sources and different biogeochemical processes governing perchlorate behavior in groundwater. Moreover a recent study has found that small amounts of perchlorate and other contaminants may be added during disinfection by municipal water treatment facilities that employ sodium hypochlorite [45]. For the sake of clarity, we note that Italian bottled water is not subjected to pre-treatment procedures, such as disinfection techniques that can result in perchlorate production, or processing steps that include carbon absorption and can remove perchlorate from the water.…”
Section: Resultsmentioning
confidence: 99%
“…The perchlorate ion is found in sodium hypochlorite solutions, and similar to the chlorate ion, perchlorate concentration increases over time (Pisarenko et al., ; Snyder, Stanford, Pisarenko, Gilbert & Asami, ; Stanford, Pisarenko, Snyder, & Gordon, ). The rate of perchlorate formation is a second‐order reaction, dependent on hypochlorite and chlorate concentrations (Gordon & Tachiyashiki, ; Snyder et al., ).…”
Section: Mechanisms Involved In the Formation Of Inorganic Chlorine Dbpsmentioning
confidence: 99%